Festival Ambalawi Fashion Street Carnival sebagai Media Kebudayaan dan Ekonomi Kreatif - Jaenab; Nurul Huda; Taufik Kurrahman; Rahmat Maulidin; Imam Mahyudin; Dea Ananda (Indo Publishing, 2025)
The Ambalawi Fashion Street Carnival Festival was held through a collaboration between Nipa KKN students and the Ambalawi Sub-district Head as a strategic platform to promote local culture while driving the community's creative economy. The event, which took place on Tuesday, August 12, 2025, at 2:00 PM in Ambalawi, featured traditional clothing, typical Bima woven motifs, and a bazaar of processed products from Nipa KKN students. By utilizing the momentum of the 80th Indonesian Independence Day celebration, this festival presented a cultural parade in the first modern carnival concept in Ambalawi, which was enthusiastically welcomed by the Ambalawi sub-district government and its staff, students, and the community. In addition to strengthening cultural identity, this event empowered local MSMEs such as weavers, accessory craftsmen, and culinary actors. The collaboration between students, local government, and cultural communities reflects synergy towards sustainable development based on education, culture, and the creative economy.